(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this paper we present about Mysticism and Romanticismin the works of Kahlil Gibran and William blake. Poetry and art are twins. Bothare the offspring of suffering and joy. Gibran translated Blake’s “Innocenceand Experience” into a “Tear and a Smile.” Nevertheless, the unending drama ofhuman existence unfolds itself in the pages of both men. Only the elected andgifted soul is capable of creativity, of reading the world differently, and ofrebelling against evil clothed in a lamb’s garment.